Formation of epitaxial Hf digermanide/Ge(001) contact and its crystalline properties. (22nd June 2018) - Nakatsuka, Osamu; Suzuki, Akihiro; McVittie, James; Nishi, Yoshio; Zaima, Shigeaki
Abstract: We have investigated the crystalline and electrical properties of the epitaxial Hf digermanide (HfGe2 )/Ge contact prepared through the rapid thermal annealing (RTA) of a TiN/Hf/Ge(001) sample. Detailed X-ray diffraction measurements demonstrate the formation of an epitaxial HfGe2 layer on a Ge substrate and clarified the orientation relationship between epitaxial HfGe2 and Ge. The surface morphology and interface structure of Hf germanide layers were observed using atomic force microscopy and scanning electron microscopy. The sheet resistance of the Hf germanide layer decreases with increasing RTA temperature and is low owing to the formation of an epitaxial HfGe2 layer.